Muscle fatigue induced by exercise simulating the work rate of competitive soccer - Rahnama, N.; Reilly, T.; Lees, A.; Graham-Smith, P. (Journal of Sports Sciences, 2003)
Fatigue represents a reduction in the capability of muscle to generate force. The aim of the present study was to establish the effects of exercise that simulates the work rate of competitive soccer players on the strength of the knee extensors and knee flexors. Thirteen amateur soccer players (age 23.3+/-3.9 years, height 1.78+/-0.05 m, body mass 74.8+/-3.6 kg; mean+/-s) were tested during the 2000-2001 soccer season. Muscle strength of the quadriceps and hamstrings was measured on an isokinetic dynamometer. A 90 min soccer-specific intermittent exercise protocol, incorporating a 15 min half-time intermission, was developed to provide fatiguing exercise corresponding in work rate to a game of soccer. The exercise protocol, performed on a programmable motorized treadmill, consisted of the different intensities observed during soccer match-play (e.g. walking, jogging, running, sprinting). Muscle strength was assessed before exercise, at half-time and immediately after exercise. A repeated-measures analysis of variance showed significant reductions (P < 0.001) in peak torque for both the quadriceps and hamstrings at all angular velocities (concentric: 1.05, 2.09, 5.23 rad x s(-1); eccentric: 2.09 rad x s(-1)). The peak torque of the knee extensors (KE) and knee flexors (KF) was greater before exercise [KE: 232+/-37, 182+/-34, 129+/-27, 219+/-41 N x m at 1.05, 2.09 and 5.23 rad x s(-1) (concentric) and 2.09 rad x s(-1) (eccentric), respectively; KF: 126+/-20, 112+/-19, 101+/-16, 137+/-23 N x m] than at half-time (KE: 209+/-45, 177+/-35, 125+/-36, 214+/-43 N x m; KF: 114+/-31, 102+/-20, 92+/-15, 125+/-25 N x m) and greater at half-time than after exercise (KE: 196+/-43, 167+/-35, 118+/-24, 204+/-43 N x m; KF: 104+/-25, 95+/-21, 87+/-13, 114+/-27 N x m). For the hamstrings:quadriceps ratio, significant changes were found (P < 0.05) for both legs, the ratio being greater before than after exercise. For fast:slow speed and left:right ratios, no significant changes were found. We conclude that there is a progressive reduction in muscle strength that applies across a range of functional characteristics during exercise that mimics the work rate in soccer.